(3GdQSGdI GdLGeYI PGJ GdahGFO GdfGaYIs - (3eSdeI Hf CMeO Hf bGSe Hf YHO Gddg GdeLQjWj, CHh GdbGSe,J (B398 (3g` s
(3ChdgG (B:s
(3hLOJ HNW CHj QMeI Gddg GYde jG CNj HCfg deG cGfJ QJHI GdEfSGfjI eJhSWI Hjf GdehLhOGJ s
(3BNQgG (B:s
(3dgG ai GdSehGJ heG ai GdCQV heG HjfgG heG JMJ GdKQi JeJ GdQSGdI GdLGeYI s
(3ChQGb ai ChdgG hBNQgGs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B224 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B234s
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
Keywords: (3GdadSaI hGdefWbs